The rare reason for massive lactic aciduria and mitochondrial disorders: combined oxidative phosphorylation deficiency type 23 (COXPD23) - Akar, Halil Tuna; Akduman, Hasan; Kolkıran, Abdülkerim; Taşadelen, Elifcan; Aycan, Nur (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
Mitochondrial respiratory chain dysfunction and impaired oxidative phosphorylation are rare but significant causes of mitochondrial diseases in children, presenting with diverse clinical features. Combined oxidative phosphorylation deficiency type 23 (COXPD23), an autosomal recessive disorder due to GTPBP3 gene mutations, typically manifests as lactic acidosis, hypertrophic cardiomyopathy, and encephalopathy. This case report describes a male infant born at 35 weeks gestation, who exhibited severe lactic aciduria and hypotonia but no cardiomyopathy, which is atypical for COXPD23. Genetic analysis revealed a novel homozygous missense variant in the GTPBP3 gene. Despite intensive metabolic and supportive treatments, the patientʼs condition worsened, leading to death on the 23rd day. This case emphasizes the need to consider mitochondrial cytopathies in neonates with persistent metabolic acidosis and hyperlactatemia and highlights the importance of early genetic screening for accurate diagnosis and management.
Keywords: Neonatal period; Neonatology; Mortality